An empirical survey on the awareness of construction developers about green buildings in Macedonia - Stojanovska-Georgievska, Lihnida; Sandeva, Ivana; Spasevska, Hristina (National Library of Serbia, 2018)
Green construction is becoming priority in developing a new scope to the construction itself. It emerges from the inevitable need to raise the environmental concern and to make effort to build sustainable, by balancing between the conservation of the environment and maintaining prosperity in development. Green design does not only make a positive impact on public health and the environment, it also reduces operating costs, enhances building and organizational marketability, increases occupant productivity, and helps create a sustainable community. This survey aims at determining the stage of knowledge and awareness about green buildings among most involved stakeholders. The survey targets basic understanding about green building and reveals the opinion about the advances and possible barriers for regulated construction of green buildings. This survey is conducted using the method of structured questionnaires and is based on the responses of 181 construction developers including designers, architects, civil engineers, technicians, workers in construction industry, investors, as well as legal representatives (decision makers). The overall results show high level of familiarization with the concept of green buildings (more than 75% of the respondents), and even higher percentage in expressing support of the idea for green buildings (less than 6% gave negative answers). The results obtained from three structured groups of questions (awareness, advantages & barriers, and possible areas for intervention) are discussed in comprehensive manner, by additional comparison with the results for global trends, in order to analyze thoroughly the current stage of awareness about green buildings in Macedonia.